REMINISCENCES OF LICENSES IN BIOLOGICAL SCIENCES ON SCIENCE TEACHING IN BASIC EDUCATION - Lunardi, Larissa; Emmel, Rúbia (Práxis Educacional, 2020)
This study is an excerpt from a Master's Degree in Science Teaching research, which aims to analyze the research-formation-action (IFA) model in the initial formation processes of Science and Biology teachers, and its relationship with the methodologies of the Science teaching. This research presents a qualitative and documentary approach, and the analysis comes from narrative writings in logbooks, produced by the 14 undergraduates, enrolled in the curricular component Practical as Curricular Component III in a course in Biological Sciences, during the first class of the course. Teaching Internship. The research analysis was carried out using the principles of Textual Discourse Analysis (DTA): unitarization, categorization and communication. From the ATD, different categories emerged and, with this, metatexts that originated two reflective spirals: A) Stories and memories of the undergraduate students about Science classes during Basic Education; and B) Teachers' memories of science teachers. Therefore, the narrative writings allow the graduates in the IFA movement to give voice to the reminiscences involving the teaching of Sciences in Basic Education and the reflection in their process of initial formation and teacher constitution.